Identification of Slip Surfaces Using Vertical Electrical Sounding Method in Desa Seumadam for The Study of Landslide-Prone Areas - Anda, Sabrian Tri; Fajriani, Fajriani; Fajri, Haikal; Fahril, Muhammad Ari; Putra, Rachmad Almi; Fadhli, Zul (Aceh International Journal of Science and Technology, 2024)
This study explores the application of the Vertical Electrical Sounding (VES) method for identifying potential slip surfaces in the Desa Seumadam region, a known landslide-prone area. By employing geophysical techniques, the assessment has been made in order to delineate the subsurface characteristics for slip surface identification landslide volume estimation. Based on data interpretation regarding the resistivity model of the subsurface in the study area, the slip surface or weak zone is classified as a clay layer underlain by sand and clayey sand layer. The clay is identified with resistivity value varying from 7 54.5 m and located at depth of 6 to 11.68 m while the sand and clayey sand layer are categorized with resistivity value of 4 1395 m with a thickness of 11.68 m. As for the estimation of landslide volume, the calculation was made using the landslide mass volume potential approach and found that the landslide volume is estimated at around 2.139 m3. It is believed that the study not only reveals the potential slip surface of the study area but also enhances the understanding of landslide mechanisms. The findings reveal valuable insights into the geological factors contributing to landslides, facilitating informed decision-making for landslide risk mitigation and land-use planning.